2020
DOI: 10.1101/2020.12.04.412155
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromatin remodeling in peripheral blood cells reflects COVID-19 symptom severity

Abstract: SARS-CoV-2 infection triggers highly variable host responses and causes varying degrees of illness in humans. We sought to harness the peripheral blood mononuclear cell (PBMC) response over the course of illness to provide insight into COVID-19 physiology. We analyzed PBMCs from subjects with variable symptom severity at different stages of clinical illness before and after IgG seroconversion to SARS-CoV-2. Prior to seroconversion, PBMC transcriptomes did not distinguish symptom severity. In contrast, changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Moderate), and in extremely severe (ICU) versus severe patients (ICU vs. Severe), which were not investigated previously using RNA-Seq of PBMCs representing different COVID-19 stages [8][9][10]12 . This analysis was performed to gain insights into genes or pathways differentially regulated during the progression of this disease from the moderate to extremely severe condition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moderate), and in extremely severe (ICU) versus severe patients (ICU vs. Severe), which were not investigated previously using RNA-Seq of PBMCs representing different COVID-19 stages [8][9][10]12 . This analysis was performed to gain insights into genes or pathways differentially regulated during the progression of this disease from the moderate to extremely severe condition.…”
Section: Resultsmentioning
confidence: 99%
“…Advances in high-throughput sequencing technologies have enabled gaining insights into the perturbations in the expression of different genes and biological pathways that result in a wide range of clinical manifestations in hosts. Although several studies have focused on differential gene expression during the SARS-CoV-2 infection [5][6][7][8][9][10][11] , these analyses are based mainly on the criteria of expression fold-change and statistical significance for identifying. It is recognized that many of the lowly expressed genes may also be biologically or medically significant but may get filtered out due to their not meeting the preset criteria.…”
mentioning
confidence: 99%
“…Accordingly, robust epigenetic and metabolic changes, which may be associated with macrophage tolerance and innate immune memory, have recently been reported in COVID-19 patients. Genome-wide CRISPR screens using SARS-CoV-2 showed that genes encoding the SWI/SNF chromatin-remodeling complex are pro-viral factors (Wei et al, 2021), and the distinct chromatin accessibility changes during virus infection were associated with COVID-19 severity (Giroux et al, 2020). Alterations of metabolic pathways, such as kynurenine, which is linked to COVID-19 severity (Nie et al, 2021;Shen et al, 2020) and sepsis (van der Poll et al, 2017), were also demonstrated.…”
Section: Immunoparalysis and Innate Immune Memorymentioning
confidence: 99%
“…Giroux group demonstrated chromatin remodeling in certain innate immune populations (CD14+ monocytes) to be associated with divergence in symptom severity and the identified transcription factors, regulatory elements, and downstream pathways. All these would be potential prognostic markers for COVID-19 infection (Giroux et al 2020).…”
Section: Histone Modificationsmentioning
confidence: 99%